Logistics mangement in coffee exporting companies in the province of Jaén - Carnero Raulich, Stalin Roberto; Maslucan Villalobos, Alexandra Nicole; Montes Tocto, Richard Ignacio; Collazos Alarcón, Mercedes Alejandrina (LACCEI, 2025)
Logistics management is essential for export companies, especially in important sectors such as the coffee industry in Peru; however, despite its influence, there are few updated studies that analyze how coffee companies manage logistics in strategic regions such as es Jaén, therefore, this study aims to analyze logistics management in these companies, addressing three key aspects: inbound logistics, internal logistics and outbound logistics, providing a theoretical and practical contribution to the sector. The research was developed under a quantitative approach, using a non-experimental and cross-sectional design, for data collection, a questionnaire of 18 questions was used, each related to a specific phase of logistics management and validated by experts in the field. area. The questionnaire was applied to 21 coffee companies in Jaén, and subsequently, the results were analyzed with the SPSS statistical software, thus revealing a high reliability of the instrument, with a value of 0.822, which demonstrates the internal consistency of the results obtained, in Since the findings indicated that, in general, the companies evaluated have efficient logistics management, however, critical areas were identified, such as storage, internal transportation, packaging and documentation, improving these processes would contribute to increasing efficiency in the use of time and resources, which in turn would strengthen the competitiveness of these companies in the international market.